(untitled) (Journal of Education and Development, 2025)
The reform of the educational system requires a developmental approach in the implementation of the curriculum. The aim of the research is to present aspect in the teaching of natural sciences, to identify the challenges and innovative opportunities during the practical implementation of the curriculum. The research is both quantitative and qualitative. It was conducted with 240 participants, including teachers (educators, trainers, coordinators) and principals, across 60 pre-university schools in Kosovo. For data collection, questionnaires with ready-made and comment answers were used, as well as interviews with principals. Participants involved in the research were asked to analyze 10 questions, with answers ready for analysis (positive or negative and to provide comments), based on key curricular issues such as: competencies, the developmental integrative approach, curricular load, or other factors. The research results at the four levels have shown aspects of the developmental approach with positive responses as follows: at the preschool level, it is 21%, at the primary level 17.71%, at the lower secondary level 21.57%, and at the upper secondary level 14%. The total data gives 18.96%, indicating positive opportunities in the continuation of the curriculum implementation. The study identified difficulties in the curriculum development approaches in 81.03%. Teachers presented obstacles in the process such as: curricular load, didactic materials and limited time, while principals highlight issues such as working conditions, professional development of staff and increased institutional responsibility. According to research, the developmental and integrated approach refers to progressive opportunities, with changes in teaching strategies and additional commitments, to eliminate obstacles to curriculum implementation in natural sciences, improve results, and increase student interest.